Cewa concepts of musical instruments - Nurse, G. T. (International Library of African Music, 1970)
In 1965 the Cewa novelist John W. Gwengwe published, ostensibly as a school text-book, a work called Kukula ndi Mwambo. The title may be interpreted either as Growth and Custom or Growing is Custom. The book explores many aspects of the development and training of the children of a Cewa village, among them their introduction of music as part of village life. For this purpose the author provides a classification of musical instruments which is remarkably similar to that of Hornbostel and Sachs. Whether this is an example of indigenous ingenuity or, as has been suggested, the outcome of one of Dr. Tracey's informative visits to Malawi, is uncertain; whatever the case, it is good evidence of the acceptability of this classification in a village milieu.
Keywords: Chewa (African people); Music; Musical instruments; Ethnomusicology; Malawi; African Music